PEMERTAHANAN IDENTITAS ETNIS MINANGKABAU OLEH PAGUYUBAN IKATAN KELUARGA MINANG SAIYO (IKMS) BALI DI KOTA DENPASAR - Nadhifa Erdianputri; Ida Ayu Alit Laksmiwati; I Ketut Kaler (Pascasarjana Universitas Hindu Indonesia, 2024)
Minangkabau is an ethnic group of migrants who have distinctive characteristics. This ethnic community has a matrilineal kinship system. This kinship system means that Minang youth do not have power over property ownership in their village. Therefore, they migrate to find a position and gain experience so that they have independence. In overseas lands they have an inherent ethnic identity given to them by people from other ethnic groups. Bali is one of the choice places for Minangkabau people to migrate. Bali is a multicultural area that is used as a stopover and even a place of domicile for various ethnicities, religions, races and even nations. The Bali Minang Saiyo Family Association (IKMS) Paguyuban is a Minangkabau community organization. In the midst of ethnic diversity in Bali, this community strives to maintain their identity and culture. This research aims to understand how the Bali IKMS community attempts to maintain Minangkabau ethnic culture in Denpasar City. In analyzing the problem, this research uses functionalism theory and a qualitative approach. Data collection techniques in research use observation, interview and literature study techniques. The data was analyzed using qualitative analysis techniques. The results of this research reveal that the Bali IKMS community plays a role in maintaining ethnic identity through organizations. Apart from that, local communities in the surrounding areas are open to the Minangkabau ethnic migrant community, so that good relations are established between local communities and the Minangkabau ethnic migrant community in Bali.